Should we ask for more than consistency of Darwinism with Mendelism?. (December 2019) - Grafen, Alan
Abstract: A nonmathematical exposition of the current status of the formal darwinism project is presented, linking it to the fundamental theorem of natural selection, which is regarded as Fisher's own 'formal darwinism project'. The purpose is to found organism-level thinking about design and adaptation, in short Darwinism, on what is known about the mechanics of genetic inheritance, in short Mendelism, and the project is to do so in as general a biological setting as possible. This view also makes sense of the name 'fundamental theorem of natural selection'. Highlights: The formal darwinism project now incorporates arbitrary class structure. The formal darwinism project now incorporates environmental uncertainty. The fundamental theorem was Fisher's formal darwinism project. The fundamental theorem shows natural selection is an improving process. Fisher's ingenious definition of fitness is explained.